Representation of Patriarchal Motherhood in “Silsilah Duka” by Dwi Ratih Ramadhany - Zakiyatul Mufidah; Erika Citra Sari Hartanto (Jurusan Sastra Indonesia, 2021)
The article attempts to scrutinize representation of motherhood in a novella “Silsilah Duka” by Dwi Ratih Ramadhani, a young Madurese writer. It tells about three female characters and their journey as mothers, which, later, create shattering events. In analyzing the data, this study applies patriarchal motherhood theory by Andrea O’Reilly. Qualitative approach with close reading method is applied. The results disclose that patriarchal motherhood is this novella is socially and culturally constructed.